2013
DOI: 10.18227/1678-7226rga.v7i1.2999
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos Antrópicos E Suas Implicações Na Bacia Hidrográfica Do Rio Carapá, Colíder –Mato Grosso/Brasil

Abstract: RESUMOO trabalho objetivou conhecer o perfil socioeconômico, as principais formas de uso do solo e as alterações no ambiente natural observadas na bacia hidrográfica do Rio Carapá, no município de Colider, Mato Grosso. Realizaram-se visitas in loco e aplicação de questionário composto por nove questões abertas. Foram entrevistados 30 camponeses em 16 diferentes comunidades rurais. Para a delimitação da área de estudo foram utilizadas informações de bases cartográficas com imagens de satélites LandSat (TM5), qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Bernasconi, Mendonça and Micol (2009), when mapping the APPs of Colíder in 2008, indicated 60% of degradation, and the precarious situation of the APPs of this municipality has also been reported by Nobre, Roque and Bampi (2013). The municipalities of this region historically have livestock farming as their main economic activity (LOVATO, 2017), where there is also a Mining Reserve that encompasses municipalities such as Peixoto de Azevedo, Novo Mundo, Nova Guarita, Matupá, Marcelândia, Terra Nova do Norte and Nova Santa Helena (MASSARO; THEIJE, 2018), with activity characterized by being conducted on the banks of rivers, resulting in erosive processes (SOUZA et al, 2008) and degradation of APPs.…”
Section: Resultsmentioning
confidence: 89%
“…Bernasconi, Mendonça and Micol (2009), when mapping the APPs of Colíder in 2008, indicated 60% of degradation, and the precarious situation of the APPs of this municipality has also been reported by Nobre, Roque and Bampi (2013). The municipalities of this region historically have livestock farming as their main economic activity (LOVATO, 2017), where there is also a Mining Reserve that encompasses municipalities such as Peixoto de Azevedo, Novo Mundo, Nova Guarita, Matupá, Marcelândia, Terra Nova do Norte and Nova Santa Helena (MASSARO; THEIJE, 2018), with activity characterized by being conducted on the banks of rivers, resulting in erosive processes (SOUZA et al, 2008) and degradation of APPs.…”
Section: Resultsmentioning
confidence: 89%
“…Among the works in the literature we can highlight the study of Nobre et al (2013) on the anthropogenic effects and its implications in the basin of Rio Carapá in Colíder, northern Mato Grosso State. The authors found that 60% of Permanent Preservation Areas are degraded.…”
Section: Discussionmentioning
confidence: 99%